Eksistensi Kesenian Tradisional Joget Dangkong Di Pulau Panjang Kota Batam - Desma Yulia (Universitas Negeri Padang, 2018)
The purposes of this research are to explain the existence of Dangkong dance as the Malay traditional art, namely; to know the socio-cultural functions of Dangkong dance in Malay society, to know the socio-cultural functions of Dangkong Dance at Panjang Island society, to explain the facts of what caused the change occurrence of the Dangkong Dance roles at Panjang island society. To achieve these purposes, the research activities will be divided into two stages, namely the library research and the field research. The library research focused on searching some books that are relevant to the research, while the field research conducted in the form of surveying the sampling of the location, observation and in-depth interview. Furthermore, the methods used in this research namely Clifford Geertz’s ethnographic analysis.The results show that Dangkong Dance as Malay traditional art consists of several elements: (1) musical accompaniment; (2) song accompaniment; (3) ornament. Dangkong Dance performance occupies the function as the entertainment art. Dangkong Dance performance also is regarded as the complementary of the core entertainment or as a cover in the entertainment. The changes of the traditional art relate with the decreasing of public interest to Dangkong Dance and rarely the Dangkong Dance performance. Factors which led to low public interest to Dangkong Dance, namely: (1) the appearance of some new entertainment facilities; (2) the emergence of the dance art appearance that appropriates with the development of modernization in Panjang Island Batam city.